Precision Medicine in Alzheimer’s Disease: Investigating Comorbid Common Biological Substrates in the Rat Model of Amyloid Beta-Induced Toxicity - Morgese, Maria Grazia; Bove, Maria; Di Cesare Mannelli, Lorenzo; Schiavone, Stefania; Colia, Anna Laura; Dimonte, Stefania; Mhillaj, Emanuela; Sikora, Vladyslav; Tucci, Paolo; Ghelardini, Carla; Trabace, Luigia (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD), one of the most widespread neurodegenerative disorder, is a fatal global burden for the elder population. Although many efforts have been made, the search of a curative therapy is still ongoing. Individuating phenotypic traits that might help in investigating treatment response is of growing interest in AD research. AD is a complex pathology characterized by many comorbidities, such as depression and increased susceptibility to pain perception, leading to postulate that these conditions may rely on common biological substrates yet to be determined. In order to investigate those biological determinants to be associable with phenotypic traits, we used the rat model of amyloid beta-induced toxicity. This established model of early phase of AD is obtained by the intracerebroventricular injection of soluble amyloid beta1‐42 (Aβ) peptide 7 days before performing experiments. In this model, we have previously reported a depressive-like phenotype associated with subtle alteration in memory processes. In light of evaluating pain perception in this animal model, we performed two different behavioral tests commonly used, such as the paw pressure test and the cold plate test, to analyze mechanical hyperalgesia and thermal allodynia, respectively. Behavioural outcomes confirmed the memory impairment in the social recognition test and, compared to sham, Aβ‐injected rats showed an increased selective susceptibility to mechanical but not to thermal stimulus. Behavioural data were then corroborated by neurochemical and biochemical biomarker analyses either at central or peripheral level. Data showed that the peptide injection evoked a significant increase in hypothalamic glutamate, kynurenine and dopamine content, while serotonin levels were reduced. Plasma Cystatin‐C, a cysteine protease, was increased while serotonin and melatonin levels were decreased in Aβ‐injected rats. Urinary levels paralleled plasma quantifications, indicating that Aβ‐induced deficits in pain perception, mood and cognitive domain may also depend on these biomarkers. In conclusion, in the present study, we demonstrated that this animal model can mimic several comorbid conditions typical of the early phase of AD. Therefore, in the perspective of generating novel therapeutic strategies relevant to precision medicine in AD, this animal model and the biomarkers evaluated herein may represent an advantageous approach.